Study of the plastic metal conforming of brass with bismut - Padilla Víctor, Eusebio Nelson Dionicio (2009)
The Bismuth Brass Material which microstructure is formed by α and β crystals presents Bismuth inclusions in the grain boun- daries and in the grain. The Bismuth-Selenium Brass Material which microstructure is formed by α and β crystals presents Bismuth inclusions in the grain boundaries and in the grain; Selenium is presented in the grain boundaries. The mechanical properties are the following: Mean Properties I II Tensile Strength, Mpa 385 387 Yield Strength, Mpa 180 175 Elongation % 38,8 40,5 Hardness, BHN 110 112 The speed of electrochemistry corrosion in mpy, according to Tafel is the following: Material I Tap Water: mpy = 0.998 NaCl Solution at 3.56% mpy = 1.065 Material II Tap Water: mpy = 0.970 NaCl solution at 3.56%: mpy = 1.105